Evidence-based innovations for policy influence in Mai Son district, Son La province, Vietnam. Cattle and pigs value chains - Dao Thu, Hang Thi; Mwema, Emmanuel; Notenbaert, An; Atieno, Mary (2024)
The CGIAR initiative on Sustainable Animal Productivity for Livelihoods, Nutrition, and Gender (SAPLING), also known as Chăn-hênh, aims at enhancing the beef cattle and pig value chains in Mai Son district, Son La province. Through Work Package 5, the initiative successfully developed evidence-based tools to promote sustainable livestock practices, reduce environmental impacts, and improve livelihoods. The Agricultural Service Center (ASC), a key Chan-henh partner in Mai Son district, played a central role in these achievements by implementing innovative livestock practices and capacity-building activities at the community level. In its official report to the Mai Son People’s Committee, ASC highlighted significant progress, including measurable improvements in livestock productivity, environmental efficiency, and the adoption of sustainable practices. The report showcased how interventions, such as improved feed utilization, biosecurity measures, and the use of advanced forages, contributed to a 55% increase in meat production while reducing greenhouse gas emissions by 25% and cutting land-use demands by 43%. These outcomes underscore the initiative’s alignment with local development priorities and its ability to balance productivity gains with environmental sustainability and socio-economic inclusion.